The Impact of Digital Technologies on the Labor Market of Belarusian Youth - Titarenko, Larissa G.; Rezanova, Ekaterina (Волинський національний університет імені Лесі Українки, 2021)
The article examines the impact of modern digitalization processes on the youth labor market in Belarus within the framework of the risk theory. This made it possible to assess the possible negative consequences of digitalization and to determine the ways to regulate them. On the empirical base of data analysis of two studies of youth, conducted with the participation of the authors, the contradictory influence of digitalization on the youth labor market is highlighted: the characteristics of the youth professional trajectories and labor values are described. The article also discusses the possibilities for the develop-ment of entrepreneurial initiatives and the information and communication environment of modern youth. Particular attention is paid to the analysis of risks in the youth labor market: the imbalance of supply and demand, unemployment, the emergence of new forms of labor relations. It is concluded that the key to the problem of balancing the youth labor market is the modernization of the education system in accordance with the requirements of digital transformation: focus on the formation of the students’ digital competencies; introduction of new information technologies (IT) in the educational process, etc. Improvement of the institutional conditions for doing business can enhance youth activity in entrepreneurship and allow young people to successfully adapt to new forms of labor relations. У статті досліджено вплив сучасних процесів цифровізації на молодіжний ринок праці в Білорусі з позиції теорії ризику. На емпіричній базі даних двох досліджень молоді виокремлено позитивні та негативні наслідки впливу цифровізації на ринок праці, охарактеризовано професійні траєкторії молоді й трудових цінностей, розглянуто можливості для розвитку підприємницьких ініціатив. Описано інформаційно-комунікаційне середовище, у якому формуються цінності білоруської молоді. Особливу увагу приділено аналізу зовнішніх і внутрішніх ризиків на молодіжному ринку праці, створених цифровізацією: дисбаланс попиту й пропозиції, структурне безробіття, нестабільні форми трудових відносин. Зниження цих ризиків може сприяти оптимізації ринку праці молоді. Зроблено висновок про необхідність модернізації системи освіти відповідно до вимог цифрової трансформації економіки (цілеспрямоване формування цифрових компетенцій молоді, упровадження дистанційних технологій в освітній процес), а також реформування законодавчих основ формування ринку праці молоді (відмова від системи розподілу, поліпшення інституційних умов ведення бізнесу та ін.). Запропоновано стратегії, спрямовані на допомогу молоді за допомогою зниження потенційних ризиків цифровізації ринку праці.
Keywords: risks of digitalization of labor; digital technologies; youth labor market; labor values; youth unemployment; new forms of employment; 316.334.22